2019
DOI: 10.1152/japplphysiol.00567.2019
|View full text |Cite
|
Sign up to set email alerts
|

Potato ingestion is as effective as carbohydrate gels to support prolonged cycling performance

Abstract: Carbohydrate (CHO) ingestion is an established strategy to improve endurance performance. Race fuels should not only sustain performance but also be readily digested and absorbed. Potatoes are a whole-food-based option that fulfills these criteria, yet their impact on performance remains unexamined. We investigated the effects of potato purée ingestion during prolonged cycling on subsequent performance vs. commercial CHO gel or a water-only condition. Twelve cyclists (70.7 ± 7.7 kg, 173 ± 8 cm, 31 ± 9 yr, 22 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
1
9
1
Order By: Relevance
“…What if the type of food ingested affects appetite and so also "calories in"? Put another way, what if the calories acquired from eating, for example, potatoes (which have a higher glycemic index [46] and act in an equivalent way to glucose gels used by elite athletes [47], but which feature prominently in healthy eating guidelines) produce a different physiological effect on dietary behaviors than, say, the same amount of calories from an avocado? If an individual is hungrier in the hours after the former compared to the latter, then the isocaloric substitution approach may nullify potentially important differences between the effects on appetite, satiety, and eating behavior of different macronutrients.…”
Section: "A Calorie Is a Calorie" And Hungermentioning
confidence: 99%
“…What if the type of food ingested affects appetite and so also "calories in"? Put another way, what if the calories acquired from eating, for example, potatoes (which have a higher glycemic index [46] and act in an equivalent way to glucose gels used by elite athletes [47], but which feature prominently in healthy eating guidelines) produce a different physiological effect on dietary behaviors than, say, the same amount of calories from an avocado? If an individual is hungrier in the hours after the former compared to the latter, then the isocaloric substitution approach may nullify potentially important differences between the effects on appetite, satiety, and eating behavior of different macronutrients.…”
Section: "A Calorie Is a Calorie" And Hungermentioning
confidence: 99%
“…Formulations of single-and multi-transportable CHO mixtures (i.e., 1.8 g•min −1 glucose; 1.2 and 0.6 g•min −1 glucose plus fructose; 0.6 and 1.2 g•min −1 glucose plus sucrose) all tended to (interaction effect p = 0.10) reduce I-FABP concentrations (area under the curve at 30 min intervals) to a similar extent relative to water during three hours of low-intensity cycling (50% Watt max ) [139]. Similarly, ingestion of 60 g•h −1 of either potato flesh puree or carbohydrate gel (2:1 maltodextrin/fructose) were able to completely attenuate the rise in I-FABP observed throughout a 2.5 h mixed-intensity cycle (2 h 60% VO 2max then a 20 km time trial in temperate conditions) [149]. To date, only one study has reported an adverse effect of CHO ingestion during exercise (1 h 70% VO 2max running in 35 • C and 12-20% RH) on GI barrier integrity, with ingestion of a multi-transportable CHO gel (18 g maltodextrin and 9 g fructose) 20-min into exercise shown to increase GI barrier integrity (I-FABP and endotoxin) loss relative to a placebo [213].…”
Section: Carbohydratementioning
confidence: 77%
“…The volume, tonicity and osmolality of CHO is equally influential. In healthy resting humans, ingestion of a single CHO-rich meal (55-70% of total kilo-calories) evokes equivocal (endotoxin [199][200][201] or slightly improved (I-FABP; [148,149]) GI barrier integrity postprandially. However, rodent experimental models of acute GI distress indicate that oral ingestion of maltodextrin [202] or sucrose [203] favorably influence GI barrier integrity.…”
Section: Carbohydratementioning
confidence: 99%
“…Further, I-FABP was not significantly different from baseline overtime, which may have been due to the exercise intensity or T env (110). During more intense cycling in ambient temperature (20 km TT, 60%-85% V _ O 2peak ), both potato flesh puree and carbohydrate gel (2:1 maltodextrin/fructose) ingestion (60 g/h) attenuated rises in I-FABP observed when only water was provided (111). When administered immediately before and every 20 min during 2 h of running (60% V _ O 2max ), both glucose and whey protein isolate ameliorated increases in I-FABP and the lactulose/rhamnose ratio (60% V _ O 2max ) in T env of 30 C, 27% RH (107).…”
Section: Carbohydratesmentioning
confidence: 81%